Evidencias geoquímicas y neomorfismo en rocas de la Formación Chachao (Valanginiano)-anticlinal Malargüe, Mendoza - Palma, R.M. (1999)
Geochemical features and neomorphism of Chachao Formation calcareous rocks (Valanginian)-Malargüe Anticline, Mendoza. The Lower Cretaceous Chachao Formation in the Malargüe anticline area consists of wackestone, packstone, grainstone and minor mudstone rich in benthic fauna (mainly bivalves) which were deposited in a shallow carbonate ramp as previous sedimentological studies have proposed. Standard petrographic, XRD, SEM, cathodoluminiscense and trace element determinations composition of micrite and microsparite mosaic crystals were undetaken in order to characterize their original mineralogy. The SEM shows that the mud fraction is composed of a mosaic texture of subhedral to anhedral micrite and microsparite crystals, both showing similar features such as smooth (unpitted) surfaces and lack of aragonite relicts. Crystal morphology also rules out the possible presence of aragonite. These features together with the microfabric, low Sr content (average: 592 ppm) of both micrite and microsparite point to an original high-magnesium calcite composition of the muds. Geochemical data from the micrite and microsparite of the mud-supported rocks of the Chachao Formation show two contrasting trends : decreasing-upward Sr and Na concentrations and increasing-upward Mg and Mn concentrations. The loss of Sr and Na are related to mineralogical stabilization of metastable carbonate particles involving the inversion of high-magnesium calcite to low-magnesium calcite, whereas local dolomitization in the upper part of the studied sequence has formed dolomite crystals showing different stages of dissolution due to meteoric and marine water influences. © 1999 Asociación Geológica Argentina.